El comercio justo y la comercialización de prendas de vestir en el centro comercial popular La Condamine - Moreira Tulcán, Jazmin Alexandra (2024)
ABSTRACT: The main objective of this report is to analyze the impact of fair trade on clothing marketing in the popular shopping center La Condamine. The problem lies in the instability of the fair trade system, which affects the income of traders. Additionally, there are other adverse factors, such as price competition, the growth of informal traders, and a need for more information about the benefits of fair trade. Methodologically, a descriptive and field approach was used through direct data collection from a population of 276 individuals, including internal staff, intermediaries, and producers. The hypothetico-deductive method was employed through field and descriptive research. The results highlighted that instability in the fair-trade system complicates income generation for traders, posing a significant challenge. They are also affected by factors such as price competition, increasing informal traders, and lack of information about the principles and benefits of fair trade. The hypothesis posed in the research provided a solid basis to assert that fair trade significantly impacts the marketing of clothing in the popular shopping center La Condamine through the chi-square test. Strategies were designed, such as alliances with local producers, staff training, and obtaining fair trade certifications. The proposal included enhancing marketing through collaborations, supplier control, sustainable technologies, regular trade fairs, promotion of recycling, and transparent labeling. In the discussion of results, aspects of fair-trade theory were highlighted, emphasizing the need to improve practices to effectively adhere to these principles. Keywords: fair trade, marketing, strategies, La Condamine.